ANALISIS KEKUATAN MEKANIK KOMPOSIT LIMBAH PLASTIK RECYCLE SINGLE USE DAN SERBUK KAYU - Tsalsa Aundry; Aswan Munang (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Material development can minimize the impact on the environment during its life cycle. The life cycle starts from the composition of raw materials, production processes, use, and recycling systems. The composite is prepared using plastic straw waste material and wood dust using a polyester resin matrix. It is making composite specimens by compressing molding using a 12-ton capacity hydraulic press. Preparation of specimens with three different volume fractions. Specimen one (30% plastic straw, 70% wood dust), box specimen (40% plastic straw, 40% wood dust, and 20% polyester matrix), and specimen three (70% polyester matrix, 30% wood dust). Tensile testing was done six times using ASTM D3039 standards with a Computer Servo hydraulic universal testing machine. Impact testing was done six times with ASTM D256 using a Charpy impact tester machine. Based on the test results, it can be seen that the material composition of 40% wood dust, 40% plastic straw, and 20% polyester matrix has optimal tensile and impact test strength. The tensile and impact test results were 16 N/ and 1.27 Joules respectively. The combination of bonds between matrix and material fibers with three composition variations can be used as an alternative in developing advanced and environmentally friendly materials.